Analysis of inhibitors of cataract surgery using phacoemulsification method At Smec Medan Hospital in 2018 - Nasution, Fajarudin; Ginting, Daniel; Tarigan, Frida Lina (Proceeding - Sari Mutiara Indonesia International Conference on Health, 2018)
Cataracts are a major cause of vision and blindness not only in Indonesia but also in the world (Ministry of Health, 2015). It is estimated that more than 50% of blindness is caused by cataracts. Phacoemulsification today is more widely used because the most recent cataract surgery method and is preferred because it uses a small incision technique, this causes the incidence of complications related to lower incision wounds, faster healing and visual rehabilitation than procedures that require incisions. the greater one. Tana's research in 2009 stated that the rate of cataract surgery in Indonesia was still low, namely for the Sumatra region as much as 14%. The study aimed to analyze the inhibitors of cataract surgery using phacoemulsification method at SMEC Medan Hospital in 2018. The study was designed using a cross sectional approach in 84 respondents. The results showed that there were significant relationships between work, fearful behavior of operations, access to health services, and access to ease of information with cataract surgery with phacoemulsification methods at Smec Hospital in 2018. There was a significant relationship between behaviors feeling no need for surgery with cataract surgery procedures Phacoemulsification at Smec Hospital in 2018. Feeling afraid of surgery is the main obstacle to cataract surgery with phacoemulsification method at Smec Hospital in 2018. It is recommended for cataract patients who will be able to improve their knowledge and prepare mentally and physically well in dealing with cataract surgery, so as to reduce patient anxiety about cataract surgery better.